2014
DOI: 10.1590/s1415-43662014000600009
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidade espacial de parâmetros físico-químicas do solo e biofísicos de superfície em cultivo do sorgo

Abstract: O conhecimento da variabilidade espacial das propriedades do solo e das culturas é importante para as tomadas de decisão sobre o manejo agrícola. Objetivou-se, neste trabalho, avaliar a variabilidade espacial de parâmetros químicos e físicos do solo e biofísicos de superfície de área cultivada com sorgo. O estudo foi conduzido em área de 12 ha de um Argissolo Vermelho Amarelo distrófico. A amostragem de solo georreferenciada e a medição da condutividade elétrica do solo foram realizadas antes do plantio do sor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
11
1
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 19 publications
6
11
1
6
Order By: Relevance
“…On the other hand, mapping soil properties with higher variability can be less accurate than soil properties with lower variability. Trends in the variation of soil attributes obtained in this study are consistent to those observed by Bernardi et al (2014) for several soil parameters.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…On the other hand, mapping soil properties with higher variability can be less accurate than soil properties with lower variability. Trends in the variation of soil attributes obtained in this study are consistent to those observed by Bernardi et al (2014) for several soil parameters.…”
Section: Resultssupporting
confidence: 89%
“…Remote sensing (RS) is another PA tool in which acquired images are transformed into vegetation indexes, which may be related to some crop variables (Schellberg et al, 2008;Bernardi et al, 2014;Escribano Rodríguez et al, 2014). Satellite-derived vegetation indexes have been widely used to estimate crop and grassland biomass; RS provides temporal and spatial patterns of ecosystem change and has been used to estimate the biophysical characteristics of crops and grasslands (Moges et al, 2004;Numata et al, 2007;Schellberg et al, 2008;Silva Júnior et al, 2013;Bernardi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the spatial variability of yield and physical properties of the soil, as well as the study of the temporal variability when properly available to farmers who adopt precision agriculture, can improve the management options and enable modern agriculture that is economically competitive and environmentally sustainable (Molin & Rabelo, 2011;Bernardi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Research on the spatial dependence structure of agricultural georeferenced variables, such as chemical and physical soil properties and crop yield, is an analysis tool which provides information to support a decision in favour of better management of production areas (BORSSOI et al, 2011;GREGO et al, 2011;URIBE-OPAZO et al, 2012;NESI et al, 2013;ASSUMPÇÃO et al, 2014;BERNARDI et al, 2014). This can be accomplished by means of geostatistical techniques that retrieve from a set of sample elements, information about the spatial variation of the phenomenon in the whole area through the construction of thematic maps of variability (DIGGLE & RIBEIRO JUNIOR, 2007).…”
Section: Introductionmentioning
confidence: 99%